PENJATUHAN PUTUSAN PEMIDANAAN KEPADA PELAKU TINDAK PIDANA PENCURIAN DENGAN KEKERASAN DALAM KEADAAN MEMBERATKAN (Studi Putusan Nomor 64/Pid.B/2013/PN.Bdw) - Relinawati Daya (Jurnal Panah Hukum, 2023)
Theft is an action taken by a person or group to take other people's goods without the owner's permission. One of the crimes of theft that has been examined and tried by the Bondowoso District Court is decision number 64/Pid.B/2013/PN.BDW. The type of research used is normative legal research with approach methods, namely legislation approach, case approach and analytical approach. Data was collected using secondary data obtained through library materials consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data analysis used is descriptive qualitative analysis and the conclusion is drawn using the deductive method. Based on the findings of the research and discussion, it can be concluded that the Imposition of Sentencing Decisions to Perpetrators of the Crime of Theft With Violence In Aggravating Circumstances (Study of Decision Number 64/Pid.B/2013